Dialect-Localized Animated Dubbing as Place-Based Cultural Geography Media for Indonesian High Schools - Donny Pramudya; Wijiono; Zainudin; Guntur Priyabumi Atmo Kutdarko (Future Space: Studies in Geo-Education, 2026)
The rapid advancement of technology in the twenty-first century has changed students’ learning patterns, particularly among Generation Z, who prefer smartphones and digital media than conventional textbooks and are more comfortable interacting with teachers through technology-based platforms. Therefore, learning media plays an essential role in supporting effective instruction and assisting teachers in delivering learning materials. This study aims to develop high school geography learning media in the form of customized animated dubbing focused on local Malang cultural content. The novelty of this research lies in content localization through dialect-specific dubbing and culturally accurate visual representations, distinguishing it from generic educational videos. This approach integrates local wisdom into audio-visual narratives, strengthens students’ sense of place, and addresses the limited availability of contextualized digital resources within the Independent Curriculum. The media development followed the ADDIE model, including analysis, design, development, implementation, and evaluation. Prior to implementation, expert validation showed a media feasibility score of 90% and a material validation score of 81.25%, both categorized as very feasible. The product was tested on 28 students of Class XI 6 at SMAN 1 Gondanglegi using purposive sampling. Learning effectiveness was measured using the Normalized Gain (N-Gain), with a pretest mean of 68.93 and a posttest mean of 76.79, resulting in an N-Gain of 0.25, indicating low-to-moderate improvement. These results indicate that the developed media is feasible and supports learning improvement when used as a supplementary tool, supported by positive teacher responses (90.62%) and student responses (85.87%).